Pengendalian Kualitas Produk Raw Glass Mirror Dengan Metode Statistical Process Control (SPC) Di PT. DEF - Kusdiani, Merlin Erinda; Sukanta, Sukanta (Fakultas Teknik Universitas Tulang Bawang, 2025)
A company cannot be separated from its customers or the products it makes. To improve production quality, the company controls product quality so that production activities can run well and smoothly. The company sets certain standards for its products, where each sample taken is tested first to find out whether the product produced meets the standards. So this research was conducted to analyze the quality control of Raw Glass Mirror products using the Statistical Process Control (SPC) Method. There are 5 types of defects analyzed, namely Bubble, Stone, Tin, Knot, and Drip. The factors that cause this type of defect are human, machine, method, material and environmental factors. Thus, the proposed improvement given by researchers is to provide routine training to all machine operators, carry out regular maintenance, select raw materials before use and check environmental conditions during the production process. Keywords: Quality Control, Product Defect, Statistical Process Control (SPC)